FMCR 2020
DOI: 10.47746/fmcr.2020.1609
|View full text |Cite
|
Sign up to set email alerts
|

HIV and SARS-CoV-2 Coinfection in A Term Pregnancy

Abstract: The novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the cause of the clinical syndrome COVID-19. Data on SARS-CoV-2 infection in pregnant women is rapidly accumulating and will help improve clinical guidelines for treatment. It is currently unknown if infection with human immunodeficiency virus (HIV) predisposes pregnant women to serious illness from SARS-CoV-2 infection. The greatest risk factors for pre-disposing patients with HIV to de-novo virulent viral infections includes non-adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To date multiple studies outlining the management of COVID-19 disease during pregnancy have been released. But there have been a few reports regarding the outcomes of mothers co-infected with SARS-CoV-2 and HIV [13]. A study in South Africa reported that pregnant women were associated with severe illness and a significant risk of maternal death in women with high-risk pregnancies including HIV.…”
Section: Discussionmentioning
confidence: 99%
“…To date multiple studies outlining the management of COVID-19 disease during pregnancy have been released. But there have been a few reports regarding the outcomes of mothers co-infected with SARS-CoV-2 and HIV [13]. A study in South Africa reported that pregnant women were associated with severe illness and a significant risk of maternal death in women with high-risk pregnancies including HIV.…”
Section: Discussionmentioning
confidence: 99%